Investigation techniques into the state of stress of reinforced concrete buildings - Mohd. Ghazali, Mohd. Zulkifli (1991)
This paper presents the results of the investigation into the problems related with structural appraisal of reinforced concrete buildings and the possibility of devising simple techniques for early detection and monitoring of potential problematic state of stress in critical elements. The basic formulation of the research problem which came from deep thought of the Simple Hooke's law in the theory of elasticity and the realization of the non-linear state of most materials at higher state of strain, was to be developed into an applied tool for determining stress levels in existing reinforced concrete building which is under duress. Early research results have indicated that there is potential in this simple mechanism such as to enable the technique to be used widely for structural appraisal purposes. The paper also explain certain behavior of RC element when subjected to common conditions associated with structural appraisal methods.